Abiotic Formation of an Amide Bond via Surface‐Supported Direct Carboxyl–Amine Coupling. (15th December 2021) - Yang, Biao; Niu, Kaifeng; Haag, Felix; Cao, Nan; Zhang, Junjie; Zhang, Haiming; Li, Qing; Allegretti, Francesco; Björk, Jonas; Barth, Johannes V.; Chi, Lifeng
Abstract: Amide bond formation is one of the most important reactions in biochemistry, notably being of crucial importance for the origin of life. Herein, we combine scanning tunneling microscopy and X‐ray photoelectron spectroscopy studies to provide evidence for thermally activated abiotic formation of amide bonds between adsorbed precursors through direct carboxyl–amine coupling under ultrahigh‐vacuum conditions by means of on‐surface synthesis. Complementary insights from temperature‐programmed desorption measurements and density functional theory calculations reveal the competition between cross‐coupling amide formation and decarboxylation reactions on the Au(111) surface. Furthermore, we demonstrate the critical influence of the employed metal support: whereas on Au(111) the coupling readily occurs, different reaction scenarios prevail on Ag(111) and Cu(111). The systematic experiments signal that archetypical bio‐related molecules can be abiotically synthesized in clean environments without water or oxygen. Abstract : Combined scanning tunneling microscopy and X‐ray photoelectron spectroscopy studies provide evidence for thermally activated abiotic formation of amide bonds between adsorbed precursors through direct carboxyl–amine coupling under ultrahigh‐vacuum conditions by means of on‐surface synthesis.